Novel electrospun fibres of amphiphilic organic-inorganic graft copolymers of poly(acrylonitrile)-graftpoly( dimethylsiloxane) for silicone composite reinforcement - Bayley, Gareth Michael (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD)--Stellenbosch University, 2011.